Organic light-emitting device and display device

By designing a boron nitrogen compound with a twisted structure, connecting the BN luminescent skeleton core unit to the B-containing bridging group, the problem of rare boron nitrogen MR-TADF materials in the prior art and difficulty in the luminescent layer film having horizontal dipole orientation is solved, and high efficiency and high color purity of OLED devices are achieved.

CN119816094AActive Publication Date: 2025-04-11JIHUA LAB
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510291340.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

In the prior art, there are few types of multi-resonance thermally activated delayed fluorescent molecules (MR-TADF) materials suitable for solution processing, and the luminescent layer film is difficult to have a horizontal dipole orientation in the wet process, resulting in low optical coupling output efficiency.

Method used

By connecting multiple BN luminescent skeleton core units to B-containing bridging groups, a boron nitrogen compound with a twisted structure is designed to improve its solubility and film formation uniformity in organic solvents, and to regulate the emission peak position by introducing the core B-containing structure to enhance horizontal dipole orientation.

Benefits of technology

It realizes efficient dissolution and uniform film formation of luminescent materials, improves the horizontal dipole orientation performance of the luminescent layer film, improves the efficiency and color purity of OLED devices, and suppresses efficiency roll-off, spectral redshift and widening.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816094A_ABST
    Figure CN119816094A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electroluminescence, and discloses an organic electroluminescent device and a display device. The structure of the boron-nitrogen compound is as shown in a formula I: # imgabs0 # formula I; the compound is prepared from specific raw materials through the processes of boronizing retaining ring reaction, boron esterification reaction, Suzuki coupling reaction and the like. The novel boron-nitrogen compound provided by the invention can be applied to a solution processing OLED (Organic Light Emitting Diode) process as a narrow-spectrum light-emitting material, and the introduction of multiple light-emitting cores and bridging groups of the novel boron-nitrogen compound is beneficial to the realization of regulation and control of the emission peak position of the material, so that the material disclosed by the invention shows green light required by practical application; the film-forming property of the boron-nitrogen compound is improved, and a formed light-emitting layer film has higher horizontal dipole orientation performance, so that the efficiency of a device is improved; meanwhile, the color purity of the light-emitting device based on the boron-nitrogen compound is obviously improved, the concentration dependence is relatively weak, and the process window can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electroluminescence, and in particular relates to an organic electroluminescent device and a display device. Background Art

[0002] As consumers' requirements for display quality on display screens continue to increase, the next generation of ultra-high-definition display has become the goal that current display technology is constantly pursuing. Organic light-emitting materials with narrow spectrum luminescence characteristics are conducive to achieving a higher display color gamut and have become a research hotspot in recent years. On the other hand, compared with vacuum evaporation technology, printing display technology has the characteristics of high material utilization, unlimited substrate size, and no need for large-size fine metal masks, which has unique advantages in medium and large-size display technology.

[0003] The emitting layer (EML) is the core part of the OLED device and largely determines the specific display performance of the OLED display. The external quantum efficiency (EQE) is a core parameter for judging the performance of the OLED device. It is mainly determined by the internal quantum efficiency (IQE) of the luminescent material and the light coupling output efficiency (ηout). First of all, in terms of internal quantum efficiency, TADF materials with a small single-triplet energy level difference can effectively utilize triplet excitons to achieve luminescence, and in theory can achieve 100% exciton utilization. The multi-resonance thermally activated delayed fluorescence molecules with a boron nitrogen (BN) skeleton also have a high quantum yield. In terms of light coupling output efficiency, it is difficult for the emitting layer film to have a horizontal dipole orientation in the wet process, which makes its light coupling output efficiency low. Multiple Resonance-induced Thermally Activated Delayed Fluorescence (MR-TADF) based on a boron-nitrogen (BN) skeleton is an organic light-emitting material with narrow spectrum luminescence characteristics and high efficiency. In the field of organic electroluminescence, the light-emitting material is a key factor in determining the performance of OLED devices. However, there are currently few types of boron-nitrogen materials suitable for solution processing, and more breakthroughs are urgently needed.

[0004] In summary, the development of multi-resonance thermally activated delayed fluorescent molecules with a boron nitrogen (BN) skeleton with good solution processing properties and enabling them to have a certain horizontal dipole orientation is of great significance to the development of the printed OLED industry. Summary of the invention

[0005] The object of the present invention is to solve the deficiencies of the prior art. Based on this, the first aspect of the present invention provides an organic electroluminescent device, comprising a light-emitting layer, wherein the light-emitting layer comprises a light-emitting guest material and a host material, wherein the light-emitting guest material comprises a boron nitrogen compound, and its structure is shown in Formula I: Formula I; Among them, R1 is hydrogen or methyl, and R2 is selected from one of hydrogen, C1-C12 alkyl, C1-C12 alkoxy, C3-C10 cycloalkyl, phenyl, carbazolyl, diphenylamino, diphenylamino substituted by at least one C1-C12 alkyl, and carbazolyl substituted by at least one C1-C12 alkyl.

[0006] Compared with the existing boron-nitrogen luminescent materials, the present invention connects multiple BN luminescent skeleton core units to the B-containing bridging group, so that the molecular structure presents a special twisted structure, thereby achieving the following effects: First, the molecular structure of the boron-nitrogen compound of the present invention can improve the solubility of organic materials in organic solvents, and thus can be applied to solution processing technology; second, the BN molecular skeleton has a multiple resonance effect, which can make it have a narrow spectrum characteristic, thereby improving its displayed color purity, and at the same time having a higher luminous efficiency; third, the twisted molecular structure is conducive to inhibiting the accumulation of luminescent molecules, thereby reducing the efficiency roll-off of the device and the spectral red shift and spectral broadening caused by molecular accumulation; fourth, by introducing a core B-containing structure, the luminescent material as a whole can have a certain charge transfer luminescence characteristic, and the emission peak position of the luminescent material can be regulated; fifth, the overall molecular structure of the luminescent material provided by the present invention is conducive to achieving an improvement in the horizontal dipole of the luminescent layer.

[0007] In some preferred implementations, the structure of the boron nitrogen compound is one of M1-M12: .

[0008] In a more preferred embodiment, the structure of the boron-nitrogen compound is M9 or M11, and the maximum current efficiency can reach 73.8 cd / A and 76.3 cd / A, respectively, and the current efficiency at 1000 nit brightness can reach 53.0 cd / A and 55.2 cd / A, respectively.

[0009] In addition, the present invention provides a method for preparing the above-mentioned boron nitrogen compound, comprising the following steps: Raw material 1 and raw material 2 are reacted to obtain intermediate 1, and the reaction formula is as follows: ; The specific process is as follows: potassium tert-butoxide (2.2 eq) is dissolved in anhydrous DMF to form a mixed solution a, a carbazole raw material (i.e., raw material 2, 2.2 eq) is dissolved in anhydrous DMF to form a mixed solution b, and the mixed solution b is slowly dripped into the mixed solution a under nitrogen conditions, and stirred at room temperature for 2 hours to form a mixed solution c; a substituted 1-bromo-2,6-difluorobenzene raw material (i.e., raw material 1, 1.0 eq) is dissolved in anhydrous DMF to form a mixed solution d, and the mixed solution d is added dropwise into the mixed solution c, and then heated at 140°C for 24 hours to form a mixed solution e; after cooling, the mixed solution e is poured into excess ice water, the precipitate is collected by filtration, and the intermediate 1 is obtained by column chromatography.

[0010] The intermediate 1 is subjected to a borylation ring reaction to generate intermediate 2. The reaction formula is as follows: ; The specific process is as follows: the intermediate 1 (1.0 eq) is dissolved in tert-butylbenzene to form a mixed solution f, which is cooled to 0°C in an ice-water bath, and tert-butyl lithium (2.0 eq) is slowly added to the mixed solution f under nitrogen protection, and heated at 60°C for 2 hours to form a mixed solution g; boron tribromide (2.0 eq) is added to the mixed solution g at -30°C, and stirred at room temperature for 1 hour to form a mixed solution h, and N,N-diisopropylethylamine (2.0 eq) is added to the mixed solution h at 0°C, and heated at 130°C for 6 hours to form a mixed solution g. Methanol is added to the mixed solution g to neutralize the remaining boron tribromide in the mixed solution, and the mixed solution g is extracted and separated by column chromatography to obtain the intermediate 2.

[0011] The intermediate 2 is subjected to borate esterification reaction to generate intermediate 3. The reaction formula is as follows: ; The specific process is as follows: catalyst [Ir(COD)(OCH3)]2 (0.01 eq), 4,4-di-tert-butylbipyridine (dtbpy) (0.02 eq), intermediate 2 (1.0 eq) and bis(pinacol)diboron (B2Pin) (1.0 eq) are added to ultra-dry tetrahydrofuran solvent, then nitrogen is bubbled for 5 minutes, and then heated under reflux and stirred for 24 hours under a nitrogen atmosphere. After cooling to room temperature, the mixture is purified by column chromatography to obtain intermediate 3.

[0012] The intermediate 3 and the raw material 3 are subjected to Suzuki coupling reaction to generate intermediate 4. The reaction formula is as follows: ; The specific process is as follows: intermediate 3 (1.0 eq), raw material 3 (1.1 eq), tetrabutylammonium bromide and tetrakis(triphenylphosphine)palladium are added to aqueous potassium carbonate solution and tetrahydrofuran, heated to reflux for 8 hours under a nitrogen atmosphere, extracted and separated by column chromatography to obtain intermediate 4.

[0013] The intermediate 4 is reacted with the raw material 4 to generate the boron nitrogen compound. The reaction formula is as follows: ; The specific process is as follows: the intermediate 4 (2.2 eq) is dissolved in ether or tetrahydrofuran, n-butyl lithium (2.4 eq) is added dropwise at -78 °C, the mixture is warmed to 0 °C and stirred for 40 min-60 min, and then a toluene solution containing 1.0 eq of 9,10-dibromo-9,10-diboranthracene is added dropwise at -78 °C, the mixture is returned to room temperature and stirred for 8-12 h, the reaction solution is concentrated, and then extraction and column chromatography are performed to obtain the above-mentioned boron nitrogen compound.

[0014] The raw material 2 is one of RM2-1 to RM2-6, and the structures thereof are as follows: ; The above raw material 3 is RM3-1 or RM3-2, and its structure is as follows: .

[0015] The content of the luminescent guest material is 0.1 wt%-20 wt%, and the content of the host material (which may be mCP, mCPBC, CBP, 2,6DCzPPy or mCPCN, etc.) is 80 wt%-99.9 wt%. The organic electroluminescent device comprises an anode, a cathode and an organic thin film layer disposed between the anode and the cathode, wherein the organic thin film layer comprises the luminescent layer, an optional hole injection layer, an optional hole transport layer, one or more optional electron transport layers, and an optional electron injection layer.

[0016] More specifically, the organic electroluminescent device comprises in sequence: an anode, a hole injection layer, a hole transport layer, the light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer, and a cathode. In some other implementations, an optional hole blocking layer, an optional electron blocking layer, and an optional capping layer may also be included.

[0017] Among them, the light-emitting layer, the hole injection layer and the hole transport layer can be prepared by a spin coating process or an inkjet printing process, and the electron transport layer, the electron injection layer and the cathode can be prepared by a vacuum evaporation process.

[0018] A second aspect of the present invention provides a display device comprising the above-mentioned organic electroluminescent device.

[0019] The beneficial effects of the present invention are as follows: the novel boron nitrogen compound proposed in the present invention can be applied to the solution-processed OLED process as a narrow-spectrum luminescent material, and the introduction of its multiple luminescent cores and bridging groups is conducive to the regulation of the emission peak position of the material, so that the material of the present invention exhibits the green light required for practical applications; the film-forming performance based on the boron nitrogen compound is improved, and the formed luminescent layer film has a higher horizontal dipole orientation performance, which is conducive to improving the device efficiency; at the same time, the light-emitting device based on the boron nitrogen compound has a significant improvement in color purity, and has a weaker concentration dependence, which can improve the process window. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The figure shows the structure of an organic electroluminescent device, wherein 1 is an ITO anode, 2 is a hole injection layer, 3 is a hole transport layer, 4 is a light-emitting layer, 5 is a hole blocking layer, 6 is an electron transport layer, 7 is an electron injection layer, and 8 is a metal cathode. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments and drawings to clearly and completely describe the concept, specific structure and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0022] The structures of compounds M1-M12 involved in the following contents are shown below:

[0023] .

[0024] The synthetic routes of the above compounds M1-M12 are as follows: Raw material 1 and raw material 2 are reacted to obtain intermediate 1, and the reaction formula is as follows: ; Intermediate 1 is subjected to a borylation ring reaction to generate intermediate 2. The reaction formula is as follows: ; Intermediate 2 is subjected to boroesterification reaction to generate intermediate 3. The reaction formula is as follows: ; Intermediate 3 and raw material 3 are subjected to Suzuki coupling reaction to generate intermediate 4. The reaction formula is as follows: ; The intermediate 4 is reacted with the raw material 4 to generate the boron nitrogen compound, and the reaction formula is as follows: .

[0025] Among them, raw material 2 includes RM2-1 to RM2-6, and their structures are as follows: .

[0026] Raw material 3 includes RM3-1 or RM3-2, and the structures thereof are respectively as follows: .

[0027] The structures of mCPBC, PEDOT:PSS, mCP, 3NT2T, Liq, CM1, CM2, CM3, and CM4 involved in the following contents are as follows:

[0028]

[0029] .

[0030] In addition, in the following content, the mass spectra data (Mass Spectra: MS) of molecules with a relative molecular weight below 1000 were measured by Thermo Fisher's ITQ1100 ion trap gas chromatography-mass spectrometry, and the mass spectra data of molecules with a relative molecular weight above 1000 were measured by Bruker's Autoflex Speed ​​matrix-assisted laser desorption time-of-flight mass spectrometry. The machine used for elemental analysis of the final product was Elemental Analysis's Flash EA1112.

[0031] Preparation Example A boron-nitrogen compound, the structure of which is shown in compound M9; and a preparation method thereof comprises the following steps: (1) Potassium tert-butoxide (2.46 g, 22 mmol) was added to a 250 mL two-necked flask and dissolved in 50 mL of anhydrous DMF. Then, raw material 2 (RM2-3, 6.15 g, 22 mmol) dissolved in 100 mL of anhydrous DMF was slowly added thereto under a nitrogen atmosphere and stirred at room temperature for 2 hours. Then, raw material 1 (1.93 g, 10 mmol) dissolved in 30 mL of anhydrous DMF was added dropwise to the previous mixture under a nitrogen atmosphere and heated at 140 °C for 24 hours. The reaction system was cooled to room temperature and then the reaction solution was added to 2500 g of excess ice water. The precipitate was collected by filtration and separated by column chromatography using dichloromethane and petroleum ether as developing solvents to obtain intermediate 1 (5.34 g) with a yield of 75%.

[0032] (2) In a 250 mL double-necked flask, the intermediate 1 (7.12 g, 10 mmol) was dissolved in 150 mL of tert-butylbenzene, and the mixture was cooled to 0 °C in an ice-water bath. Under nitrogen protection, a solution of tert-butyllithium in n-hexane (15.4 mL, 1.3 mol / L, 20 mmol) was slowly added, and the mixture was heated to 60 °C for 2 h. The mixture was then cooled to -30 °C and boron tribromide (1.9 mL, 20 mmol) was added to the reaction mixture under nitrogen. The mixture was returned to room temperature and stirred for 1 h, and then cooled to 0 °C. N,N-diisopropylethylamine (2.8 mL, 20 mmol) was added to the reaction mixture under nitrogen, and the mixture was heated to 130 °C for 6 h. 10 mL of methanol was added to neutralize the remaining boron tribromide in the mixed solution. The reaction solution was extracted with water and dichloromethane. Dichloromethane and petroleum ether were used as developing solvents. Column chromatography was used to separate the intermediate 2 (2.63 g) with a yield of 41%.

[0033] (3) The catalyst [Ir(COD)(OCH3)]2 (33.2 mg, 0.05 mmol), 4,4-di-tert-butylbipyridine (dtbpy) (26.8 mg, 0.1 mmol), intermediate 2 (3.2 g, 5 mmol) and bis(pinacolato)diboron (B2Pin) (1.29 g, 5 mmol) were added to a 250 mL two-necked flask, and 60 mL of ultra-dry tetrahydrofuran was added thereto. After bubbling with nitrogen for 5 minutes, the mixture was heated under reflux and stirred for 24 hours under a nitrogen atmosphere. After cooling to room temperature, the reaction solution was concentrated under reduced pressure and purified by column chromatography using dichloromethane and petroleum ether to obtain intermediate 3 (3.03 g) with a yield of 79%.

[0034] (4) The catalyst tetrakistriphenylphosphine palladium (350 mg, 0.3 mmol), tetrabutylammonium bromide (0.1 mg, 0.3 mmol), the above intermediate 3 (7.68 g, 11 mmol), the raw material 3 (RM3-2, 3.42 g, mmol) and 50 mL of 1 mol / L potassium carbonate aqueous solution were added to a 250 mL two-necked flask, and then 50 mL of ultra-dry tetrahydrofuran was added thereto. The mixture was heated under reflux and stirred for 8 hours under a nitrogen atmosphere. After cooling to room temperature, the reaction solution was extracted and concentrated under reduced pressure. Column chromatography was performed using dichloromethane and petroleum ether to obtain intermediate 4 (5.85 g) with a yield of 71%.

[0035] (5) Under nitrogen atmosphere, intermediate 4 (9.05 g, 11 mmol) and 20 mL of dry ether solvent were added to a 100 mL two-necked flask. The temperature was cooled to -78 °C, and 5.5 mmol of n-butyl lithium solution was added dropwise. The temperature was restored to 0 °C and stirred for 40 min. The temperature was then cooled to -78 °C, and a toluene solution of raw material 4 (1.67 g, 5 mmol dissolved in 15 mmol of dry toluene solvent) was added dropwise. The mixture was restored to room temperature and stirred for 8 h. The mixture was then extracted and separated with dichloromethane and aqueous ammonium chloride solution. The solvent was concentrated by low-pressure rotary separation and then separated by column chromatography to obtain 1.03 g of product compound M9 with a yield of 62%.

[0036] According to the similar preparation method mentioned above, compounds M1-M8 and compounds M10-M12 were prepared; the elemental analysis (C, H and N percentage in the compounds) and mass spectrometry molecular weight data of the specific raw materials and products used are shown in Table 1.

[0037] Table 1

[0038] Boron Nitrogen Compound and Light Emitting Layer Thin Film Performance Test Experiment (1) Organic solvent solubility and moldability test Solubility test method: Take 1 mL of solvent, add the corresponding mass x of boron nitrogen compound into it, heat it at 80 °C for 2 hours, and observe whether the solution is clear and transparent. If the solution is clear and transparent, it is considered to be completely dissolved, otherwise it is considered to be incompletely dissolved.

[0039] Compounds M1, M3, M9, M11 and CM1 were selected for solubility comparison. The solvents selected were two organic solvents commonly used in solution processing (chlorobenzene and methyl benzoate). These two organic solvents included low boiling point solvents (boiling point less than 180 °C) and high boiling point solvents (boiling point greater than or equal to 180 °C), which are representative. The test results are shown in Table 2.

[0040] Table 2

[0041] As can be seen from Table 2, the present invention connects multiple BN light-emitting skeleton core units together through the central B-containing group to obtain a boron nitrogen compound with a twisted molecular structure. Compared with the unconnected boron nitrogen compound (such as CM1), the solubility of the boron nitrogen compound with a twisted molecular structure (such as M1, M3, M9, M11) of the present invention is significantly improved. The improved solubility is conducive to the application of organic materials in the printed OLED process.

[0042] Film uniformity test method: mCPBC was selected as the main material, and the light-emitting layer film was prepared by spin coating with a doping concentration of 2 wt%, and its RMS value was tested using an atomic force microscope (the RMS value can represent its film uniformity). Compounds M1, M3, M9, M11 and CM1 were selected for film uniformity comparison. The results are shown in Table 3.

[0043] Table 3

[0044] By comparing the data of the atomic force microscope test, it can be seen that the boron nitrogen compound of the present invention connects multiple BN light-emitting skeleton core units together through the central B-containing group to obtain a boron nitrogen compound with a twisted molecular structure. Compared with the unconnected boron nitrogen compound (such as CM1), the film formation uniformity of the boron nitrogen compound with a twisted molecular structure (such as M1, M3, M9, M11) of the present invention is significantly improved. Uniform film formation is conducive to improving the efficiency and stability of OLED devices.

[0045] (2) Test of horizontal dipole orientation of light-emitting layer film mCPBC was selected as the main material, and the doping concentration was 2 wt% for spin coating to prepare the light-emitting layer film. The horizontal dipole orientation of the film was tested using an angle-resolved spectrometer. Compounds M1, M3, M9, M11 were selected to compare the horizontal dipole orientation with CM1, CM2, CM3, and CM4. The results are shown in Table 4.

[0046] Table 4

[0047] By comparing the data of the horizontal dipole orientation test, it can be seen that the organic light-emitting molecule proposed in the present invention has a better horizontal dipole orientation trend than the comparison material of the mononuclear boron nitrogen compound (such as CM1), which is beneficial to achieving the improvement of device efficiency.

[0048] Example 1 An organic electroluminescent device (OLED device) having a structure as follows Figure 1 As shown, it includes in sequence: an ITO anode 1, a hole injection layer 2, a hole transport layer 3, a light-emitting layer 4, a hole blocking layer 5, an electron transport layer 6, an electron injection layer 7, and a metal cathode 8.

[0049] The following is a method for preparing a solution-processed OLED device, comprising: The prefabricated ITO glass was ultrasonically cleaned with cleaning solution, deionized water, and isopropanol for 15 minutes in sequence and placed in a 70°C oven for drying; the dried ITO glass was treated with an ultraviolet ozone cleaner for 15 minutes; then 200 microliters of Pedot:PSS solution was dripped on the ITO glass, spin-coated at a speed of 2000 rpm / min for 40 seconds, and then annealed and dried at a temperature of 150°C for 15 minutes to form a hole injection layer with a thickness of 40 nm; mCPBC was selected as the main material, and the luminescent materials M1-M12 prepared in the preparation example were selected as luminescent guests, dissolved in chlorobenzene solvent according to a certain mass ratio to form a first mixed solution, the concentration of the first mixed solution was 12 mg / mL, and a PTFE filter membrane with a filter diameter of 0.22 microns was used to filter it to form a second mixed solution, and 80 microliters of the second mixed solution was dripped on the hole injection layer, spin-coated at a speed of 1800 rpm / min for 30 seconds, and annealed and dried at a temperature of 80°C for 60 minutes to form a hole injection layer of about 40 nm. The unfinished device was transferred to the evaporation chamber and -5 In a Pa vacuum atmosphere, an electron transport layer with a thickness of 40 nm is formed at a rate of 0.05 nm / s. Here, 3NT2T is used as the electron transport layer material. An electron injection layer with a thickness of 2 nm is formed at a rate of 0.01 nm / s. Here, (8-hydroxyquinoline) lithium is used as the electron injection layer material. A cathode layer is formed at a rate of 0.02 nm / s. Here, metal aluminum is used as the cathode layer.

[0050] Finally, organic electroluminescent devices Device1-Device12 were obtained. Among them, PEDOT:PSS was used as a hole injection layer. In the light-emitting layer, the synthesized final products M1-M12 were used as luminescent guest materials, mCPBC was used as a host material (the guest material doping concentration was 2 wt%), 3NT2T was used as an electron transport material, (8-hydroxyquinoline) lithium was used as an electron injection layer, and Al was used as a metal cathode. Its structure is [ITO / PEDOT:PSS (40 nm) / mCPBC:2.0wt% M1-M12 (40 nm) / 3NT2T (40 nm) / Liq (2 nm) / Al(100 nm)].

[0051] Example 2 An organic electroluminescent device (OLED device) is prepared in the same manner as in Example 1, except that M9 is selected as the luminescent guest material and the doping concentration is changed to 5wt%, 10wt% and 20wt%. Finally, organic electroluminescent devices Device13-Device15 are obtained.

[0052] Comparative Example 1 An organic electroluminescent device (OLED device) is prepared in the same manner as in Example 1, except that PEDOT:PSS is used as a hole injection layer, CM1 is used as a luminescent guest material, mCPBC is used as a host material (doping concentration is 2 wt%), 3NT2T is used as an electron transport material, (8-hydroxyquinoline) lithium is used as an electron injection layer, and Al is used as a metal cathode. Finally, an organic electroluminescent device Compare 1 is obtained, and its structure is [ITO / PEDOT:PSS (40 nm) / mCPBC:2.0wt% CM1 (40 nm) / 3NT2T (40 nm) / Liq(2 nm) / Al(100 nm)].

[0053] Comparative Example 2 An organic electroluminescent device (OLED device) is different from Comparative Example 1 in that the doping concentration of the luminescent guest material CM1 is 5wt%, 10wt% and 20wt%, respectively. Finally, organic electroluminescent devices Compare 2-Compare 4 are obtained.

[0054] Comparative Example 3 An organic electroluminescent device (OLED device) is prepared in the same manner as in Example 1, except that PEDOT:PSS is used as a hole injection layer, CM2 is used as a luminescent guest material, mCPBC is used as a host material (doping concentration is 2 wt%), 3NT2T is used as an electron transport material, (8-hydroxyquinoline) lithium is used as an electron injection layer, and Al is used as a metal cathode. Finally, an organic electroluminescent device Compare 5 is obtained, and its structure is [ITO / PEDOT:PSS (40 nm) / mCPBC:2.0wt% CM2 (40 nm) / 3NT2T (40 nm) / Liq(2 nm) / Al(100 nm)].

[0055] Comparative Example 4 An organic electroluminescent device (OLED device) is prepared in the same manner as in Example 1, except that PEDOT:PSS is used as a hole injection layer, CM3 is used as a luminescent guest material, mCPBC is used as a host material (doping concentration is 2 wt%), 3NT2T is used as an electron transport material, (8-hydroxyquinoline) lithium is used as an electron injection layer, and Al is used as a metal cathode. Finally, an organic electroluminescent device Compare 6 is obtained, and its structure is [ITO / PEDOT:PSS (40 nm) / mCPBC:2.0wt% CM3 (40 nm) / 3NT2T (40 nm) / Liq(2 nm) / Al(100 nm)].

[0056] Comparative Example 5 An organic electroluminescent device (OLED device) is prepared in the same manner as in Example 1, except that PEDOT:PSS is used as a hole injection layer, CM4 is used as a luminescent guest material, mCPBC is used as a host material (doping concentration is 2 wt%), 3NT2T is used as an electron transport material, (8-hydroxyquinoline) lithium is used as an electron injection layer, and Al is used as a metal cathode. Finally, an organic electroluminescent device Compare 7 is obtained, and its structure is [ITO / PEDOT:PSS (40 nm) / mCPBC:2.0wt% CM4 (40 nm) / 3NT2T (40 nm) / Liq(2 nm) / Al(100 nm)].

[0057] Performance testing of organic electroluminescent devices (OLED devices) The organic electroluminescent devices Device1-Device15 prepared in Examples 1-2 and the organic electroluminescent devices Compare 1-Compare 5 prepared in Comparative Examples 1-3 were tested. The current, voltage, brightness, luminous spectrum and other characteristics of the devices were tested synchronously using a Photo Research PR 655 spectrum scanning luminance meter and a Keithley K2400 digital source meter system. The performance test of the device was carried out at room temperature and ambient atmosphere. The test results are shown in Table 5.

[0058] Table 5

[0059] By comparing the device performance of the embodiment and the comparative example in Table 5, the following conclusion can be drawn: when the boron nitrogen compound of the present invention is used as the luminescent guest material of the solution-processed OLED device, the prepared organic electroluminescent device obtains a higher maximum efficiency and maintains a better light color (half-peak width), while maintaining a higher efficiency at a higher brightness, and can effectively suppress the spectral width broadening and spectral red shift caused by the increase of the doping concentration, which is conducive to expanding the process window of the material in the device preparation and has a stronger applicability. The boron nitrogen compound of the present invention connects multiple BN luminescent skeleton core units together by containing a B-type bridging group to obtain a boron nitrogen compound with a distorted molecular structure. Compared with the unconnected boron nitrogen compound (such as CM1), when the doping concentration of the boron nitrogen compound with a distorted molecular structure of the present invention increases, the spectral broadening and red shift of the organic electroluminescent device (such as Device9, Device13-15 compared with Compare1-5) are suppressed, and the efficiency roll-off is also suppressed.

[0060] By comparing Device 7-9 with Compare 5, it can be seen that if the R2 group in the structure of the present invention is adjusted, the luminescent material of the present invention will not be able to emit green light, and the device as a whole will emit blue-green light, and the maximum current efficiency of the device will be reduced and the spectrum will be broadened.

[0061] By comparing Device 9 with Compare 6 and Compare 7, it can be seen that due to the change in the core structure, the comparative example mainly exhibits charge transfer state luminescence rather than multiple resonance luminescence, the device exhibits orange-red light, and the half-peak width becomes wider.

[0062] In summary, the boron nitrogen compound of the present invention has achieved many improvements by connecting multiple BN luminescent skeleton core units to a B-containing bridging group: the solubility in organic solvents and the film-forming uniformity are improved, the luminescent peak position is successfully regulated to the green light region and the characteristics of narrow spectrum luminescence are maintained, the obtained luminescent layer film has a horizontal dipole orientation trend, the prepared organic electroluminescent device has higher efficiency and improved efficiency roll-off, and when the doping concentration is increased, the red shift and broadening of the electroluminescent spectrum are suppressed.

[0063] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.

Claims

1. An organic electroluminescent device, characterized in that: The invention comprises a light-emitting layer, wherein the light-emitting layer comprises a light-emitting guest material and a host material, wherein the light-emitting guest material comprises a boron nitrogen compound, and the structure of the boron nitrogen compound is shown in Formula I: Formula I; Among them, R1 is hydrogen or methyl, and R2 is selected from one of hydrogen, C1-C12 alkyl, C1-C12 alkoxy, C3-C10 cycloalkyl, phenyl, carbazolyl, diphenylamino, diphenylamino substituted by at least one C1-C12 alkyl, and carbazolyl substituted by at least one C1-C12 alkyl.

2. The organic electroluminescent device according to claim 1, characterized in that: The structure of the boron nitrogen compound is one of M1-M12: 。 3. The organic electroluminescent device according to claim 2, characterized in that: The structure of the boron nitrogen compound is M9 or M11.

4. The organic electroluminescent device according to claim 1, characterized in that: The preparation method of the boron nitrogen compound comprises the following steps: Raw material 1 and raw material 2 are reacted to obtain intermediate 1, and the reaction formula is as follows: ; The intermediate 1 is subjected to a borylation ring reaction to generate an intermediate 2, and the reaction formula is as follows: ; The intermediate 2 is subjected to a boroesterification reaction to generate an intermediate 3, and the reaction formula is as follows: ; The intermediate 3 and the raw material 3 are subjected to Suzuki coupling reaction to generate intermediate 4, and the reaction formula is as follows: ; The intermediate 4 is reacted with the raw material 4 to generate the boron nitrogen compound, and the reaction formula is as follows: 。 5. The organic electroluminescent device according to claim 4, characterized in that: The raw material 2 is one of RM2-1 to RM2-6, and its structure is as follows: 。 6. The organic electroluminescent device according to claim 4, characterized in that: The raw material 3 is RM3-1 or RM3-2, and its structure is as follows: 。 7. The organic electroluminescent device according to claim 1, characterized in that: The content of the luminescent guest material is 0.1 wt%-20 wt%, and the content of the host material is 80 wt%-99.9 wt%.

8. The organic electroluminescent device according to claim 1, characterized in that: Including in order: Anode, hole transport layer, the light emitting layer, electron transport layer, cathode.

9. The organic electroluminescent device according to claim 8, characterized in that: Including in order: Anode, hole injection layer, hole transport layer, the light emitting layer, hole blocking layer, electron transport layer, electron injection layer, cathode.

10. A display device, characterized in that: An organic electroluminescent device comprising any one of claims 1 to 9.

Citation Information

Patent Citations

  • Blue light thermal activation delayed fluorescence material, synthetic method and electroluminescent device

    CN111100152A

  • Thermal activation delayed fluorescence material, preparation and applications thereof

    CN111116620A

  • Boron-nitrogen compound as well as preparation method and application thereof

    CN118307574A